The Implications of Web-Driven Diary Writing on Students’ Well-Being: A Piloting Study among University Students - Christiana Sidupa; Joice Yulinda Luke; Yella Dezas Perdani; Fransisca Hanita Rusgowanto (Borneo Educational Journal (Borju), 2022)
The present article aims to describe to what extent VBee as a web-driven diary writing app affects university students’ well-being during a month of usage. A descriptive qualitative design is used in this research as the details are described and the data obtained during the research are interpreted. This qualitative research data uses a written survey that is questionnaire. Google survey is free survey by Google to make it more practical for researchers to collect the data from the participants. The participants in the study consist of 13 English-as-a foreign-language learners in their second semester at a private university using VBee. After performing analysis on the data, it is found that mostly the students agree that by using this application they can freely express their ideas, communicate their daily thoughts and experiences, convey the students’ doubts or feelings, and build continuous interactions between students and teachers. Finally, some practical recommendations are noted.